2022
DOI: 10.1155/2022/2447461
|View full text |Cite
|
Sign up to set email alerts
|

Does Dexmedetomidine Improve or Worsen Restless Leg Syndrome under Sedation: A Case Report and Extensive Review

Abstract: Background. Restless leg syndrome (RLS) is a common neurological condition that manifests as creeping, nonpainful urges to move lower extremities and is relieved with movements of the legs. RLS is associated with comorbidities such as gastric surgery, diabetes mellitus, uremia, and iron deficiency anemia, and it is misdiagnosed in many cases. Drugs like levodopa, ropinirole, pramipexole, cabergoline, and pergolide that target the dopaminergic system have been traditionally used to treat symptoms of RLS. α2-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, local analgesia also takes effect by stimulating the α2 acceptor to regulate hypalgesia. 21,22 It was found that TWL increased significantly on the 7 th day after ligation of the sciatic nerve and continuous intraperitoneal injection in the DEX group, thereby signifying that neuropathic pain can be substantially alleviated via continuous intraperitoneal DEX injection. Dexmedetomidine can be characterized by its strong anti-nociceptive effect by directly suppressing the release of excitatory neurotransmitters (like glutamic acid) from the synaptic afferent terminus of the spinal dorsal cord.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, local analgesia also takes effect by stimulating the α2 acceptor to regulate hypalgesia. 21,22 It was found that TWL increased significantly on the 7 th day after ligation of the sciatic nerve and continuous intraperitoneal injection in the DEX group, thereby signifying that neuropathic pain can be substantially alleviated via continuous intraperitoneal DEX injection. Dexmedetomidine can be characterized by its strong anti-nociceptive effect by directly suppressing the release of excitatory neurotransmitters (like glutamic acid) from the synaptic afferent terminus of the spinal dorsal cord.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, local analgesia also takes effect by stimulating the α2 acceptor to regulate hypalgesia. 21 22…”
Section: Discussionmentioning
confidence: 99%